2023
DOI: 10.1002/art.42504
|View full text |Cite
|
Sign up to set email alerts
|

Lowering Serum Urate With Urate‐Lowering Therapy to Target and Incident Fracture Among People With Gout

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…That said, gout is associated with a moderately higher risk of fracture [40,154], and postmenopausal females have elevated risk of osteoporotic fracture. A recent study indicated that ULT that achieves the serum urate target reduces the risk of fracture in gout patients [155]. Therefore, postmenopausal gout patients with osteoporosis might benefit from treat-to-target ULT.…”
Section: Treatment Responses In Females With Goutmentioning
confidence: 99%
“…That said, gout is associated with a moderately higher risk of fracture [40,154], and postmenopausal females have elevated risk of osteoporotic fracture. A recent study indicated that ULT that achieves the serum urate target reduces the risk of fracture in gout patients [155]. Therefore, postmenopausal gout patients with osteoporosis might benefit from treat-to-target ULT.…”
Section: Treatment Responses In Females With Goutmentioning
confidence: 99%
“…In an organism, uric acid is the final metabolite produced by the degradation of purine compounds by the liver. A delicate dynamic balance is maintained through production and excretion. , Once the balance is disturbed, it can lead to a variety of diseases, such as hyperuricemia, gout, , and cardiovascular system diseases. , As the most abundant catecholamine neurotransmitter in the brain, dopamine regulates the central nervous system. The abnormal concentration of dopamine can cause neurological disorders such as Parkinson’s disease, , schizophrenia, and Tourette’s syndrome …”
Section: Introductionmentioning
confidence: 99%
“…A delicate dynamic balance is maintained through production and excretion. 1,2 Once the balance is disturbed, it can lead to a variety of diseases, such as hyperuricemia, 3 gout, 4,5 and cardiovascular system diseases. 6,7 As the most abundant catecholamine neurotransmitter in the brain, dopamine regulates the central nervous system.…”
Section: Introductionmentioning
confidence: 99%